(untitled) (Commonwealth Journal of Local Governance, 2022)
Assigning recurrent taxes on immovable property to cities, municipalities, and rural districts is a common practice around the world. The Republic of Ireland is no different, with its annual taxes on real property assigned to local government. Following the 2008 financial crisis and the austerity era that ensued, Ireland’s property taxes underwent major reform, most notably the design and implementation of a new residential property tax 35 years after abolition of the previous system of ‘rates’ on residential properties. In this paper the new or different features of Ireland’s residential property tax are outlined, including the use of self-assessment and valuation bands, innovative payment methods and also the multiple compliance mechanisms for taxpayers. While recognising the importance of country-specific and local circumstances in property tax design, the paper concludes that elements of Ireland’s new residential property tax have potential lessons for other jurisdictions contemplating similar tax reform. These relate to the key tax principles of simplicity and public acceptability, and on specific design features of assessment and valuation, and collection and compliance.